Meningkatkan Kemampuan Hasil Belajar Muatan IPA Melalui Model Discovery Learning Siswa Kelas II SDN Nglumber 1 - Indah wahyu nur cahyani; Setiawan, Agung (SEMESTA: Jurnal Ilmu Pendidikan dan Pengajaran, 2024)
This research is motivated by the fact that student learning outcomes are still low in science subjects class II at SDN Nglumber 1. This determines the learning outcomes of students whose grades are below the KKM. The discovery model can describe a substitute for growing student learning outcomes. Therefore researchers are encouraged to carry out further research on the discovery model in improving student learning outcomes. The purpose of this study was to find out how many students were able to apply the discovery model in improving student learning outcomes in science subjects at SDN Nglumber 1. The type of research used in this study was classroom action research. The subjects in this study were class II students at SDN Nglumber 1. Data collection techniques used by researchers were observation sheets, tests and documentation. Based on the results of the research carried out, it can be assumed that by applying the discovery model it can improve the learning outcomes of class II students at SDN Nglumber 1 in science subjects from before the action, cycle I, cycle II. Before the action it was known that 6 students had completed with 21% classical completeness, in cycle I it was known that 17 students had completed with 59% classical completeness, in cycle II it was known that 26 students had completed with 90% classical completeness. Therefore it can be concluded that by applying the discovery model it can improve the learning outcomes of class II students at SDN Nglumber 1 in science subjects.